2003
DOI: 10.1074/jbc.m306500200
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity of Nonhomologous DNA End-joining Mutants to VP-16 and ICRF-193

Abstract: A number of clinically useful anticancer drugs, including etoposide (VP-16), target DNA topoisomerase (topo) II. These drugs, referred to as topo II poisons, stabilize cleavable complexes, thereby generating DNA doublestrand breaks. Bis-2,6-dioxopiperazines such as ICRF-193 also inhibit topo II by inducing a distinct type of DNA damage, termed topo II clamps, which has been believed to be devoid of double-strand breaks. Despite the biological and clinical importance, the molecular mechanisms for the repair of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(70 citation statements)
references
References 54 publications
6
64
0
Order By: Relevance
“…In this scenario, overexpression of TDP1 could promote the formation of active repair complexes and more or larger repair centers, which in summary would allow a more rapid repair of both topo I-and topo II-mediated damage by homologous recombination. This scenario is the more credible, since in mammals the default mechanism for the repair of topo II-mediated DNA breaks seems to be non-homologous endjoining (33). Thus, it could well be that overexpression of TDP1 increases the capacity of a mammalian cell for the repair of topo II-mediated DNA strand breaks by a supportive up-regulation of the RAD52 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, overexpression of TDP1 could promote the formation of active repair complexes and more or larger repair centers, which in summary would allow a more rapid repair of both topo I-and topo II-mediated damage by homologous recombination. This scenario is the more credible, since in mammals the default mechanism for the repair of topo II-mediated DNA breaks seems to be non-homologous endjoining (33). Thus, it could well be that overexpression of TDP1 increases the capacity of a mammalian cell for the repair of topo II-mediated DNA strand breaks by a supportive up-regulation of the RAD52 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The idea that efficient alternative pathways (other than HR) may work to repair Top1-mediated DNA damage contrasts with the situation in yeast where HR plays essential roles in Top1 damage repair (28); specifically, several redundant pathways are involved in the initial processing of Top1 damage, but all the pathways eventually rely on HR to complete repair. Yet, even the partial contribution from HR in vertebrate Top1 damage repair would be intriguing in light of our recent finding that vertebrate Top2-mediated DNA damage (induced by Top2 inhibitors) is predominantly repaired by NHEJ, not HR (21). In yeast, HR is responsible for the repair of Top2-mediated DNA damage, whereas NHEJ has only a minor role (49).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the enzyme by Top2 inhibitors, such as VP-16 or ICRF-193, has been shown to generate DSBs (17)(18)(19)(20). We have recently shown that Top2-mediated DNA damage is predominantly repaired by the NHEJ pathway as evidenced by the observations that NHEJ mutants (LIG4 Ϫ/Ϫ and KU70 Ϫ/Ϫ cells) are extremely sensitive to Top2 inhibitors compared with wild-type or RAD54 Ϫ/Ϫ cells (21). Interestingly, the absence of Rad54 alleviated the hypersensitivity of KU70 Ϫ/Ϫ cells, suggesting that the cytotoxicity of Top2 inhibitors is enhanced by HR (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, we previously reported that Top2-mediated DNA damage is predominantly repaired by the non-homologous end-joining (NHEJ) pathway in higher eukaryotes, contrasting with the situation in yeast, where homologous recombination repairs virtually all Top2-mediated DNA damage (37,39,46,47). In mammalian cells, NHEJ and homologous recombination are the two major pathways of DSB repair, and these pathways are roughly equally important for the repair of radiation-induced DSBs (48 -51).…”
Section: Nk314mentioning
confidence: 99%